2022
DOI: 10.1094/phyto-02-21-0065-r
|View full text |Cite
|
Sign up to set email alerts
|

Joint Action of Pb1 and Pb2 Provides Dominant Complementary Resistance Against New Races of Peronospora belbahrii (Basil Downy Mildew)

Abstract: Sweet basil (Ocimum basilicum, 2n=4x=48) is susceptible to downy mildew caused by Peronospora belbahrii. Pb1 gene exhibit complete resistance to the disease. However, Pb1 became prone to disease due to occurrence of a new virulent races. Here we show that Zambian accession PI 500950 (O. americanum var pilosum) is highly resistant to the new races. From an interspecies backcross between PI 500950 and the susceptible cv ‘Sweet Basil’ we obtained, by embryo rescue, a population of 131 BC1F1 plants. This populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Other BDM resistant cultivars have been produced through interspecific hybridization of O. basilicum with O. americanum var. pilosum , leading to dominant resistance against two races of P. belbahrii (Ben-Naim & Weitman, 2021). We have observed that the downy mildew-resistant basil cultivars succumb to infection in production systems in different regions, consistent with the report of emerging pathogen races (Ben-Naim & Weitman, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other BDM resistant cultivars have been produced through interspecific hybridization of O. basilicum with O. americanum var. pilosum , leading to dominant resistance against two races of P. belbahrii (Ben-Naim & Weitman, 2021). We have observed that the downy mildew-resistant basil cultivars succumb to infection in production systems in different regions, consistent with the report of emerging pathogen races (Ben-Naim & Weitman, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…pilosum , leading to dominant resistance against two races of P. belbahrii (Ben-Naim & Weitman, 2021). We have observed that the downy mildew-resistant basil cultivars succumb to infection in production systems in different regions, consistent with the report of emerging pathogen races (Ben-Naim & Weitman, 2021). Therefore, understanding the physiological and molecular bases of host-pathogen interactions is critical to rapidly developing improved cultivars, monitoring strategies, and management practices.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic fungicides are the primary means to control downy mildew disease in basil [12][13][14][15]. Control of downy mildew disease in basil was achieved in several cases through the action of two or more genes, but the mechanism(s) of host resistance is undetermined [16][17][18]. The genome of a German isolate of P. belbahrii was sequenced and described [19].…”
Section: Introductionmentioning
confidence: 99%